2022
DOI: 10.1177/1076029620939181
|View full text |Cite
|
Sign up to set email alerts
|

Position Paper on the Management of Pregnancy-Associated Superficial Venous Thrombosis. Balkan Working Group for Prevention and Treatment of Venous Thromboembolism

Abstract: Venous thromboembolism (VTE) is a multifactorial disease that can possibly affect any part of venous circulation. The risk of VTE increases by about 2 fold in pregnant women and VTE is one of the major causes of maternal morbidity and mortality. For decades superficial vein thrombosis (SVT) has been considered as benign, self-limiting condition, primarily local event consequently being out of scope of well conducted epidemiological and clinical studies. Recently, the approach on SVT has significantly changed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
4
0
3
Order By: Relevance
“…Finally, the use of the “zero-fluoroscopy” technique and the help of new technologies allowed us to resolve the case without further complications for mother and fetus. The common femoral vein thrombosis that occurred after the first procedure is a possible complication expected after catheter ablation procedures using a venous approach; however, it is certain that the physiological hypercoagulable state that occurs during pregnancy facilitated this event [ 12 ]. Such a complex clinical case, burdened by two complications (intra-operative cardiac tamponade and post-operative femoral venous thrombosis), also required intensive multidisciplinary management, based on an accurate integration of both cardiological and gynecological critical issues.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the use of the “zero-fluoroscopy” technique and the help of new technologies allowed us to resolve the case without further complications for mother and fetus. The common femoral vein thrombosis that occurred after the first procedure is a possible complication expected after catheter ablation procedures using a venous approach; however, it is certain that the physiological hypercoagulable state that occurs during pregnancy facilitated this event [ 12 ]. Such a complex clinical case, burdened by two complications (intra-operative cardiac tamponade and post-operative femoral venous thrombosis), also required intensive multidisciplinary management, based on an accurate integration of both cardiological and gynecological critical issues.…”
Section: Discussionmentioning
confidence: 99%
“…2,22,23 The daily risk of VTE is 15 to 35 times higher in the postpartum period, as compared with nonpregnant women of the same age. [24][25][26] Most cases of PA-VTE occurred in the postpartum period (321/510, 62.9%). James et al reported that within pregnancy-related VTE, DVT accounts for approximately 75 to 80% of all VTE cases and 20 to 25% manifest as PE.…”
Section: Discussionmentioning
confidence: 99%
“…Computed Tomography Pulmonary Angiography (CTPA) has greatly improved the diagnostic approach to patients with suspected PE and is considered to be the reference imaging test, but should be used, with caution in some patients, such as patients with severe renal insufficiency, those with known allergy to contrast media, and pregnant women[ [19] , [20] , [21] ]. Additionally, ECG findings include sinus tachycardia, atrial dysrhythmia, dramatic shift in R wave axis, incomplete or complete right bundle-branch block, inferolateral ST-segment elevation, or depression, inversion of T waves in leads V1–V4, and biomarkers such as elevated D-dimers or fibrin degradation are suggestive of PE [ 9 , 13 , 19 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%